En studie av utvecklingen av drivningsnettot i skogsbruket - Lindström, Emil (SLU/Dept. of Forest Products, 2008)
This master thesis consists of an investigation of the profitability per hectare in privatly owned forest land. The investigation is based on data collected from Skogsstyrelesen, Riksskogstaxeringen and Skogsforsk. . During the last twenty years the prices on pulp wood and saw log have substantial decreased, but during the same time the the volumes from final felling have increased and the cost for felling has decreased, this investigation shows how the netprofit per hectARE after final felling has changed between year 1980-2005 This investigation shows that that the netprofit has stayed on a stable level during the years 1985-2005 even though prices pulp wood and saw log decreased. Much indicates that the demand of swedish pulp wood and saw log will continue to be strong or even stronger wich will give increased prices and an higher netprofit after final felling in the future.